GEOGRAPHIC DYNAMIC OF WORK SURMOUNTED INTO SEASONAL MIGRATIONS TO SUGARCANE PLANTATIONS IN PONTAL DO PARANAPANEMA (SP) IN THE BEGINNING OF THE 21st CENTURY - Bento, Fredi dos Santos [UNESP]; Thomaz Junior, Antonio [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, Fac Ciencias & Tecnologia, 2015)
In this turn page of the 21st century, one can notice the increasingly rapacious advance of the capital over labor, fundamental characteristic of environments remade by the productive restructuring. This process expressed the contents of historically determined territory forms of domination over the workers, and it is therefore, on this account, the precariousness that is given through migration of workers, facing few alternatives for survival, both in the urban and rural areas, from Northeast and North of Minas Gerais to Pontal do Paranapanema, in search for improved opportunities to labor. The goal of this work is to understand the territorialization of labor migration for the purview capital in the Pontal do Paranapanema region, Sao Paulo state. Thus, we also want to analyze the strategies of the sugarcane agroindustrial capital to the workers.
Keywords: labor migration; labor; territory